Innovative Originality, Profitability, and Stock Returns - Hirshleifer, David; Hsu, Po-Hsuan; Li, Dongmei (Review of Financial Studies, 2018)
We propose that innovative originality is a valuable organizational resource and that owing to limited investor attention and skepticism of complexity, greater innovative originality may be undervalued. We find that firms' innovative originality strongly predicts higher, more persistent, and less volatile profitability and higher abnormal stock returns, findings that are robust to extensive controls. The return predictive power of innovative originality is stronger for firms with higher valuation uncertainty, lower investor attention, and greater sensitivity of future profitability to innovative originality. This evidence suggests that innovative originality acts as a "competitive moat" and is undervalued by the market.